Cyprus : Request for an Arrangement Under the Extended Fund Facility. (IMF Staff Country Reports; Country Report ;, 2013)
Cyprus experienced significant internal and external imbalances owing to the European financial crisis. The oversized and weak banking sector continued to be a threat to the sovereign. Greek debt restructuring, together with loan losses of both Cyprus and Greece, resulted in the two largest banks being declared insolvent. However, the authorities have taken unprecedented steps to address the country's banking problems. Temporary administrative controls have been taken to preserve financial stability, while the Extended Fund Facility (EFF) arrangement has been aimed to stabilize the financial system and achieve fiscal sustainability.